IMPLEMETASI APLIKASI MOBILE PENGENALAN KAMPUS PADA MASA PANDEMI COVID-19 - Putu Bagus Adidyana Anugrah Putra; Viktor Handrianus Pranatawijaya; Efrans Christian; Widiatry Widiatry (Universitas Palangka Raya, 2022)
PKKMB is a place to raise awareness of the importance of understanding globalization and the industrial revolution 4.0. The introduction of the campus canbe done by introducing the rooms on campus by providing a location point usingmaps so that it can make it easier to identify the location of the rooms on campus. The research method used is determining the scope of research, consulting, studying related literature, and using the Extreme Programming method as asoftware development method. This application uses the Mobile platform and theJavaScript programming language with the React Native framework.